Glycosaminoglycan and versican deposits in taxane‐induced sclerosis. (17th August 2015) - Okada, K.; Endo, Y.; Miyachi, Y.; Koike, Y.; Kuwatsuka, Y.; Utani, A.
Abstract : What's already known about this topic? Taxane‐induced sclerosis occurs dose dependently; however, little information on the pathogenesis of scleroderma is currently available. What does this study add? We analysed collagen type I, hyaluronan and versican, and revealed that administration of taxane increased the amount of versican, which led to oedema and sclerosis in our patients. Summary: Docetaxel and paclitaxel are widely used in the treatment of various malignant neoplasms. Taxane‐induced sclerosis is dose‐dependent and usually not generalized. Little information on the pathogenesis of scleroderma is currently available. Here, we report a case of generalized scleroderma and a case of early‐stage oedematous sclerosis, both of which presented with intense versican deposits after administration of taxane for angiosarcoma.